IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE PARAGRAPH THROUGH DRAW LABEL CAPTION TECHNIQUE FOR CLASS XB OF SMA SARASWATI SINGARAJA IN THE ACADEMIC YEAR 2014/2015 - ., I Gusti Ngurah Wahyu Danuarta Yoga; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
ABSTRAK Penelitian ini bertujuan untuk meningkatkan kemampuan siswa dalam menulis paragraf deskriptif melalui penggunaan "Draw Label Caption Teknik". Subjek penelitian ini adalah siswa kelas XB SMA Saraswati Singaraja. Ada 20 siswa sama sekali, yang terdiri dari 10 laki-laki dan 10 perempuan. Penelitian ini dirancang dalam bentuk kelas berbasis penelitian tindakan dengan dua siklus. Setiap siklus memiliki tiga sesi dan setiap sesi yang terlibat perencanaan, tindakan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa melalui penerapan Draw Label Caption Teknik, kompetensi siswa dalam menulis paragraf deskriptif ditingkatkan. Perbaikan bisa dilihat dari data kualitatif dan kuantitatif ditemukan dalam penelitian ini. Data kuantitatif dapat dilihat dari nilai rata-rata siswa yang meningkat dari 57,75 (pre-test) untuk 67,5 (post-test 1 di siklus 1). Keberhasilan pelaksanaan undian Label Caption Teknik diperoleh ketika melakukan siklus kedua, di mana nilai rata-rata siswa meningkat dari 67,5 (post-test 1) ke 78 (post-test 2). Data kuantitatif didukung oleh analisis data kualitatif menunjukkan bahwa siswa lebih tertarik dan antusias dalam menulis setelah penerapan Teknik Menggambar Label Caption. Kata Kunci: Deskritif Paragraf, Draw Label caption Teknik ABSTRACT This study aimed at improving students’ ability in writing descriptive paragraph through the use of “Draw Label Caption Technique”. The subjects were the students of class XB of SMA Saraswati Singaraja. There were 20 students altogether, comprising of 10 males and 10 females. This study was designed in the form of classroom based action research with two cycles. Each cycle had three sessions and each session involved planning, action, observation, and reflection. The result of the study showed that through the implementation of Draw Label Caption Technique, the competency of the students in writing descriptive paragraph improved. The improvement could be seen from the qualitative and quantitative data found in this study. The quantitative data could be seen from the students’ mean score which improved from 57.75 (pre-test) to 67.5 (post-test 1 in cycle 1). The success of the implementation of Draw Label Caption Technique was gained when conducting the second cycle, in which the students’ mean score improved from 67.5 (post-test 1) to 78 (post-test 2). The quantitative data were supported by qualitative data analysis showed that the students were more interested and enthusiastic in writing after the application of Draw Label Caption Technique. Key word: Descriptive Paragraph, Draw Label Caption Technique. keyword : Descriptive Paragraph, Draw Label Caption Technique